2021
DOI: 10.1186/s12920-021-01140-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrative multi-omics identifies high risk multiple myeloma subgroup associated with significant DNA loss and dysregulated DNA repair and cell cycle pathways

Abstract: Background Despite significant therapeutic advances in improving lives of multiple myeloma (MM) patients, it remains mostly incurable, with patients ultimately becoming refractory to therapies. MM is a genetically heterogeneous disease and therapeutic resistance is driven by a complex interplay of disease pathobiology and mechanisms of drug resistance. We applied a multi-omics strategy using tumor-derived gene expression, single nucleotide variant, copy number variant, and structural variant pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Our previous study indicated that cell adhesion is inhibited and EMT is enhanced in MM patients 16 . However, the role of E2F2 in the pathogenicity of MM in general and its involvement in MM cell adhesion in particular was explored only by a few studies 29,30 . In this study, we found that aberrant E2F2 expression was closely associated with poor prognosis and advanced clinical stages in MM patients.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Our previous study indicated that cell adhesion is inhibited and EMT is enhanced in MM patients 16 . However, the role of E2F2 in the pathogenicity of MM in general and its involvement in MM cell adhesion in particular was explored only by a few studies 29,30 . In this study, we found that aberrant E2F2 expression was closely associated with poor prognosis and advanced clinical stages in MM patients.…”
Section: Discussionmentioning
confidence: 60%
“…16 However, the role of E2F2 in the pathogenicity of MM in general and its involvement in MM cell adhesion in particular was explored only by a few studies. 29,30 In this study, we found that aberrant E2F2 expression was closely associated with poor prognosis and advanced clinical stages in MM patients. Concurrently, we discovered that E2F2 was significantly highly expressed in MM cells and enhanced EMT and cell migration.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Patient-level transcriptomic data and clinical information, including cytogenetics and progression/survival outcomes, were assessed. RNA extraction, library preparation, and sequencing for the Multiple Myeloma Research Foundation (MMRF), CC-4047-MM-010 and CC-220-MM-001, have been described previously ( Walker et al, 2018 ; Gooding et al, 2021 ; Ortiz Estevez et al, 2021 ). NDMM patient data from the MMRF (N = 348) was used as discovery, and Toulouse [ N = 127, all t(4:14) patients] as replication cohorts.…”
Section: Methodsmentioning
confidence: 99%
“… 6 , 7 Gene expression signatures have also been shown to transition to those that indicate higher risk as disease progresses. 8 …”
Section: Introductionmentioning
confidence: 99%